ER stress and calcium-dependent arrhythmias - Hamilton, Shanna; Terentyev, Dmitry (Frontiers in Physiology, 2022)
Sarcoplasmic reticulum (SR) plays the key role in cardiac function as the major source of Ca that activates cardiomyocyte contractile machinery. Disturbances in finely-tuned SR Ca release by SR Ca channel ryanodine receptor (RyR2) and SR Ca reuptake by SR Ca-ATPase (SERCa2a) not only impair contraction, but also contribute to cardiac arrhythmia trigger and reentry. Besides being the main Ca storage organelle, SR in cardiomyocyte performs all the functions of endoplasmic reticulum (ER) in other cell types including protein synthesis, folding and degradation. In recent years ER stress become recognized as an important contributing factor in many cardiac pathologies including deadly ventricular arrhythmias. This brief review will therefore focus on ER stress mechanisms in the heart and how these changes can lead to pro-arrhythmic defects in SR Ca handling machinery.